Kinetoplastid Membrane Protein-11 as a Vaccine Candidate and a Virulence Factor in Leishmania - de Mendonça, Sergio Coutinho Furtado; Cysne-Finkelstein, Léa; Matos, Denise Cristina de Souza (Frontiers in Immunology, 2015)
Kinetoplastid membrane protein-11 (KMP-11), a protein present in all kinetoplastid protozoa, is considered a potential candidate for a leishmaniasis vaccine. In Leishmania amazonensis, KMP-11 is expressed in promastigotes and amastigotes. In both stages, the protein was found in association with membrane structures at the cell surface, flagellar pocket and intracellular vesicles. More importantly, its surface expression is higher in amastigotes than in promastigotes and increases during metacyclogenesis. The increased expression of KMP-11 in metacyclic promastigotes, and especially in amastigotes, indicates a role for this molecule in the parasite relationship with the mammalian host. In this connection, we have shown that addition of KMP-11 exacerbates L. amazonensis infection in peritoneal macrophages from BALB/c mice by increasing interleukin (IL)-10 secretion and arginase activity while reducing nitric oxide (NO) production. The doses of KMP-11, the IL-10 levels and the intracellular amastigote loads were strongly, positively and significantly correlated. The increase in parasite load induced by KMP-11 was inhibited by anti-KMP-11 or anti-IL-10 neutralizing antibodies, but not by isotype controls. The neutralizing antibodies, but not the isotype controls, were also able to significantly decrease the parasite load in macrophages cultured without the addition of KMP-11, demonstrating that KMP-11-induced exacerbation of the infection is not dependent on the addition of exogenous KMP-11 and that the protein naturally expressed by the parasite is able to promote it. All these data indicate that KMP-11 acts as a virulence factor in L. amazonensis infection.